Piloting film-based intervention on santri's perception towards striving for academic success: findings from Kampung Santri, Kudus Regency - Muna, Nailil; Widiyati, Elok; Wulandari, Diyah Fitri (Universitas Islam Sultan Agung, 2023)
This study is performed based on concerns that knowledge dichotomy in traditional Islamic boarding schools has not received the serious attention it deserves. In contrast to modern pesantren where santri receives both religious and non-religious knowledge, most traditional pesantren in Jekulo, Kudus regency only emphasizes religious knowledge as their core curriculum. Our preliminary study in 2022 suggested that the majority of student santri in Jekulo, Kudus regency showed unfavorable perceptions towards pursuing higher education despite being offered financial aid and academic mentorship. Our current task is to introduce film-based intervention and document its effect on santri's perception change towards academic success. Although the use of film-based intervention to change perception and reduce stigma has been profound in the field of clinical psychology, its application in a nonclinical setting is still understudied. Using Social Comparison Theory (Festinger, 1954) as our analytical framework, we propose that historical film can be introduced as an alternative point of reference for our subject. Respondents were selected using purposive sampling (n=20). Pre- and post-studies are provided to document santri's perception change toward striving for academic success. The results of this study confirm that film intervention can act as positive stimuli in the process of perception changes among santri by presenting relatable cinematic historical experiences as an alternative social reference. However, a lack of a role model and a shared perception toward academic success in santri's immediate environment can hinder the process